Growth Response and Production of Several Sweet Corn Varieties (Zea mays saccharata Sturt) on NPK Fertilizer Giving - Abdul Wachid; Jefri Alamsyah (Nabatia, 2018)
Sweet corn is one of the economically valuable agricultural commodities. From year to year the production value has increased as in 2015 the harvested area was 3.79 million / ha with a production of 19.61 million / ha. This study aims to determine the effect of NPK fertilizer and sweet corn varieties on growth and production. This research was carried out on the land of Jiken Village, District Reinforcement. Sidoarjo and in the Agrokomplek Laboratory, Faculty of Agriculture, Muhammadiyah University of Sidoarjo from March to July 2018. This research used factorial randomized block design (RBD) with 2 factors, factor 1: NPK fertilizer 100 kg / ha (M1), 200 kg / ha (M2), and 300 kg / ha (M3). Factor 2: ASIA 86 F1 (V1) sweet corn varieties, BONAZA F1 (V2), and TALENTA (V3). Of these two factors, 9 treatment combinations were repeated and 3 replications were repeated so that 27 experimental units were obtained. The results showed that there was a response between NPK fertilizer and several varieties of sweet corn, NPK fertilizer treatment showed that NPK fertilizer was able to increase the row of unsuspecting seeds, while in some varieties sweet corn was able to increase weighted cob, weightless cornballs, length of cropping cob. The number of planting seeds and the number of rows of seeds.